V0.05 - Valuation of D-wall remedial works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the V0.05 - valuation of D-wall remedial works of Brac University new campus development project .